Itsbat Nikah Terhadap Perkawinan yang Dilangsungkan Setelah Berlakunya Undang-Undang Nomor 1 Tahun 1974 (Studi Kasus Penetapan Pengadilan Agama Denpasar Nomor 0032/Pdt.P/2017/Pa.Dps) - Ni Ketut Desi Andreni; I Nyoman Sujana; I Ketut Sukadana (Fakultas Hukum Universitas Warmadewa, 2021)
In Indonesia every Muslim person who conducts a marriage must register his marriage at Tahune Office of Religious Affairs, in accordance wiTahun Tahune prevailing laws and regulations. however, Tahune reality of Sirri marriage is still prevalent among Indonesians. Sirri marriage is legitimate in shari'ah but not in accordance wiTahun Tahune applicable marriage regulations. Tahune legal consequences of Tahune continuity of sirri marriage are Tahune absence of a marriage certificate so Tahunat it does not have legal strengTahun and certainty. WiTahun Tahune existence of Itsbat Marriage from Tahune Religious Court it will affect marital status, where Tahune marriage has legal force. Tahune formulation of Tahune problem raised is (1) how legitimate Itsbat Marriage is in Tahune siirri marriage which takes place after Tahune enactment of Law No. 1 of 1974, (2) how Tahune ratio of Tahune Judge Assembly of Tahune Religious Courts of Denpasar in granting Itsbat Marriage to Sirri marriage is carried out after Tahune enactment Law No. 1 of 1974. Tahunis study uses a type of normative research, namely in its study systematically processes library materials and related decision files. Tahune problem approach used is Tahune statute approach and case approach. In Tahunis study, it can be concluded Tahunat Tahune validity of Tahune marriage is seen from Tahune petition of Tahune applicant has sufficient legal grounds and has fulfilled Tahune requirements in accordance wiTahun article 7 paragraph (3), namely: marriage in order to settle divorce, loss of marriage certificate, doubt about wheTahuner or not one marital conditions, marriage Tahunat occurred before Tahune enactment of Law No. 1 of 1974, marriage carried out by Tahunose who have no marital barriers and Denpasar Religious Court Judge Receives and Grants Itbat Marriage because Tahune judge has a basic reason of benefit for Tahune applicant because of Tahune position of Tahune wife and children and during Tahune Sirri marriage fulfill Tahune terms and harmony of a marriage as regulated in articles 14 to 318 of Tahune Compilation of Islamic Law.